Manusia dan Pendidikan dalam Sudut Pandang Filsafat Pendidikan Islam: Literature Review - dilla Fadhillah (Universitas Muhammadiyah Tangerang, 2022)
BSTRACTHumans as creatures created by God have the characteristics and potentials given by God. With the potential that humans have, will provide progress and goodness for themselves and others. Humans are equipped with reason that can be used to think, because humans are perfect creatures. Humans are appointed as caliphs on earth in order to be able to manage the wealth on earth and knowledge. This study aims to describe the extent to which the position and benefits of humans are seen from the philosophy of Islamic education. The method used in this study is a literature review study, using literature data obtained from scientific journal references. The results of literature review research, God gives humans the potential in the form of senses and reason to think that other creatures of God do not have. This potential is the basis for humans to carry out the task of being a caliph with the destiny attached to it. Humans have reason and mind that can be useful for conducting studies and producing a new theory in advancing education.